2010
DOI: 10.1074/jbc.m109.086660
|View full text |Cite
|
Sign up to set email alerts
|

Negative Autoregulation of GTF2IRD1 in Williams-Beuren Syndrome via a Novel DNA Binding Mechanism

Abstract: The GTF2IRD1 gene is of principal interest to the study of Williams-Beuren syndrome (WBS). This neurodevelopmental disorder results from the hemizygous deletion of a region of chromosome 7q11.23 containing 28 genes including GTF2IRD1. WBS is thought to be caused by haploinsufficiency of certain dosage-sensitive genes within the deleted region, and the feature of supravalvular aortic stenosis (SVAS) has been attributed to reduced elastin caused by deletion of ELN. Human genetic mapping data have implicated two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
26
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 32 publications
(30 reference statements)
4
26
1
Order By: Relevance
“…The GTF2IRD1 upstream region (GUR) contains three GGATTA binding sites and EMSA studies have shown that all three are required to achieve high-affinity GTF2IRD1 binding (Palmer et al 2010). This may explain why GTF2IRD1 was readily isolated from the artificial triplicated bait constructs of the original yeast one-hybrid assays.…”
Section: Introductionmentioning
confidence: 98%
“…The GTF2IRD1 upstream region (GUR) contains three GGATTA binding sites and EMSA studies have shown that all three are required to achieve high-affinity GTF2IRD1 binding (Palmer et al 2010). This may explain why GTF2IRD1 was readily isolated from the artificial triplicated bait constructs of the original yeast one-hybrid assays.…”
Section: Introductionmentioning
confidence: 98%
“…23,24 Both lines were maintained on a C57BL/6J background and homozygous Gtf2ird1 tm1Hrd and wild-type siblings were produced in the same litters from heterozygous parents and housed together in identical conditions. The Gtf2ird1 tm1Hrd line was used to assess hearing capacity and heterozygous and homozygous mutant mice are hereinafter referred to as Gtf2ird1 − /+ and Gtf2ird1 −/− , respectively.…”
Section: Materials and Methods Micementioning
confidence: 99%
“…Gtf2ird1 is expressed strongly during skeletal muscle development, but is downregulated in mature muscle (Palmer et al, 2007). Studies on Gtf2ird1 knockout mice (Palmer et al, 2010;Howard et al, 2012) have so far failed to reveal fiber type changes, which may reflect very low levels of adult expression. By contrast, Gtf2i mRNA is relatively abundant in adult skeletal muscle tissue (Roy et al, 1997) and therefore TFII-I is the best candidate for such a role.…”
Section: Subcellular Localization Of Gtf2ird2 Gtf2ird1 and Tfii-imentioning
confidence: 99%
“…Conservation of the RDs between orthologs or between family members is much higher than any other regions of the protein, suggesting that these domains constitute an essential functional element. Some of the RDs within GTF2IRD1 have been shown to have sequencespecific DNA binding properties (Polly et al, 2003;Vullhorst and Buonanno, 2005) and GTF2IRD1 protein can bind to its own promoter region via simultaneous usage of two RDs making contact with two independent DNA binding sites in the GTF2IRD1 promoter (Palmer et al, 2010). RD2 of TFII-I has also been associated with sequence-specific DNA binding properties (Cheriyath and Roy, 2001;Roy, 2001).…”
mentioning
confidence: 99%
See 1 more Smart Citation